Perioperative analgesia in decreasing the incidence and or severity of phantom pain-non-randomised observational study between intravenous morphine versus intramuscular diclofenate - Chon, Chong Kuan (2006)
PURPOSEOFTHESTUDY To evaluate the perioperative intravenous morphine and intramuscular diclofenate in reducing the incidence of phantom limb pain as well as the severity of phantom pain following lower limb amputation. In addition, to evaluate the association between phantom limb pain and the pain suffered before the amputation, the duration of diabetic mellitus and the duration of various feet or legs problems prior to amputation. METHOD This was a non-randomsed observational study involving a total 55 patients. 27 patients were selected for intravenous morphine infusion. The patients' blood pressure, heart rate, respiratory rate, sedation score, blood oxygen saturation were monitored closely. The other 28 patients were selected for intramuscular diclofenate. The drug was given to those patient who had pain score at 2 or more before operation and at regular dose after amputation. The rescue intramuscular tramadol was added if the pain was not adequately controlled in diclofenate group. Both medications were continued till day-3 post-amputation. The characteristic, intensity and location of pain encountered before analgesia, after analgesia and after amputation was documented. The modified numerical pain score wasused to quantify the intensity of pain. The phantom sensation, phantom pain and stump pain following lower limb amputation was identified in both groups. The patients were followed up at one week, 1, 3 and 6 months after amputation via phone. RESULTS Patients in both groups experienced comparable pain intensity before and after the operation (p > 0.05). However, two patients in diclofenate group required rescue i/m tramadol 50 mg for post-amputation pain control. Overall, 50 out of 55 patients (90%) experienced phantom limb sensation and 33 patients (60%) encountered phantom pain after amputation. Twenty one patients (75%) out of 28 in diclofenate group had phantom limb pain compared with 12 patients ( 44%) out of 27 in morphine group. The phantom sensation in diclofenate and morphine group was 89% and 92% respectively. In 16 patients with phantom limb pain (48%), the symptom subsided within 6 months. Most of the phantom pain encountered was low pain score and only 2 patients required medical treatment. Patients in morphine group was 0.176 time (odd-ratio) less likely to develop phantom limb pain as compared to diclofenate group (p < 0.05). Intravenous morphine significantly reduced the severity of phantom limb pain after adjusting possible confounding factors like sex, age, race and presence or absence of diabetic mellitus (p < 0.05). The maximal phantom pain score in morphine and diclofenate groups was 1.57 and 2.37 respectively. The severity of pre-analgesic prun and the duration of various leg and foot problem encountered prior to amputation did not significantly relate to phantom pain. However, the the longer history of diabetic mellitus had less risk or incidence of phantom pain (p =0.03). CONCLUSION This study showed perioperative intravenous morphine infusion reduced the incidence and severity of phantom limb pain as compared to intramuscular diclofenate.